2010
DOI: 10.1148/rg.302095728
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Assessment of Brain Arteriovenous Malformations: What Clinicians Need to Know

Abstract: Brain arteriovenous malformations (AVMs) are abnormal vascular connections within the brain that are presumably congenital in nature. There are several subgroups, the most common being glomerular type brain AVMs, with fistulous type AVMs being less common. A brain AVM may also be a part of more extensive disease (eg, cerebrofacial arteriovenous metameric syndrome). When intracranial pathologic vessels are encountered at cross-sectional imaging, other diagnoses must also be considered, including large developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(108 citation statements)
references
References 61 publications
(66 reference statements)
3
103
0
2
Order By: Relevance
“…26 Image-update rates in DSA in our study ranged from 2 to 8 frames per second. At the expense of a higher patient dose, even higher frame rates are possible with modern conventional angiography units.…”
Section: Discussionmentioning
confidence: 84%
“…26 Image-update rates in DSA in our study ranged from 2 to 8 frames per second. At the expense of a higher patient dose, even higher frame rates are possible with modern conventional angiography units.…”
Section: Discussionmentioning
confidence: 84%
“…The picture (cross sectional CT or MRI) in large developmental venous anomalies is that of enhancement of the dilated medullary veins which is described as a caput medusa or an inverted umbrella. In dural arterio-venous fistulas, dilated cortical veins which manifest as abnormal enhancing tubular structures or flow voids within the cortical sulci with no true nidus within the brain parenchyma are seen and in Moyamoya disease, there is the presence of tiny flow voids arising from the basal cisterns and extending into the basal ganglia or the thalamus with no true nidus embedded within the brain parenchyma and no dilated vessels (11).…”
Section: Discussionmentioning
confidence: 99%
“…therefore, our therapeutic goal in this study was to reduce hemorrhage risk 12,18 . a large body of evidence has shown that the therapeutic strategy for aneurysms with coexisting aVMs depends on the aneurysm type and the particular clinical characteristics present 16,17,18 . When treating ruptured aneurysms with coexisting aVMs, the common idea is that associated aneurysms are high-risk factors, which should be given priority for treatment 1,9,18 .…”
Section: Clinical Outcomementioning
confidence: 99%